Coming back to life : the permeability of past and present, mortality and immortality, death and life in the ancient Mediterranean - Frederick S. Tappenden (McGill University Library & Archives, 2017)
The lines between death and life were neither fixed nor finite to the peoples of the ancient Mediterranean. For most, death was a passageway into a new and uncertain existence, and many perceived the deceased to continue to exercise agency among the living. Even for those more skeptical of an afterlife, notions of